Linkages between industry, agriculture, growth, renewable energy and the environment and the role of institutional quality, evidence from selected South and East Asian economies - Guo Chun Lao; Guang Qiang Luo (Energy Exploration & Exploitation)
This study aims to reveal the influence of industrial progress and agricultural value addition on environmental harm and explores how the unique moderating role of institutional quality handles this association; using the panel ARDL approach on a panel of South and East Asian economies from 1980 to 2020. The baseline model proposes that for each 1% increase in agricultural added value and industrial progress, carbon dioxide emissions may fluctuate considerably positively by 0.563% and 0.758% respectively. In the long term, the plausibility of the upturned U-shaped association between economic growth and carbon dioxide emissions in South and East Asian economies has been confirmed in the analysis. The use of renewable energy considerably condenses long-term emission levels. Institutional quality is found to have a strong moderating effect on the link between the main model regressors (renewable energy use, industrial growth, GDP per capita, and agricultural value addition) and CO 2 emissions. Institutional quality supports the enhancement of industrial and agricultural capabilities and the improvement of environmental worth. Finally, the threshold results indicate that the influence of the main regression variables of the model (renewable energy utilization, industrial growth, per capita GDP, and agricultural added value) on carbon dioxide emissions has fully penetrated the institutional quality level. Strong, high-quality institutions, rather than weak institutions, can improve the aptitude of industry and agriculture to mitigate environmental degradation. In this pursuit, it becomes increasingly important to develop policies that support renewable energy based on institutional values.